Susceptibility and resistance of Gram-negative bacteria to a novel antimicrobial agent TGV-49 - Tetz, Victor V.; Kardava, Kristina M.; Vecherkovskaya, Maria F.; Leyn, Semen A.; Elane, Marinela L.; Osterman, Andrei L.; Tetz, George V. (Frontiers in Antibiotics, 2025)
IntroductionAntimicrobial resistance remains a major global public health challenge that necessitates novel drugs with a low resistance rate.MethodsHerein, we evaluate TGV-49, a novel broad-spectrum antimicrobial agent, against multidrug-resistant Gram-negative bacteria, including ESKAPE pathogens (Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae) and pathogens from agriculture that infect humans (Ralstonia solanacearum and Aeromonas hydrophila).ResultsTGV-49 was highly effective in overcoming resistance to conventional antibiotics. The experimental evolution of A. baumannii using a morbidostat revealed minimal development of resistance.ConclusionOur findings suggest TGV-49 as a potential alternative for combating MDR infections in clinical and agricultural settings.